(untitled) (Eurasian Journal of Media and Communications, 2024)
In this article, we will consider the methods and goals of conducting information wars on the Internet, give examples of the main strategies and technological components of conducting an information conflict. We will talk about what exactly is done to implement information influence on people and manipulate their consciousness.